Critical Success Factor Analysis of Asphalt Pavement Works of North Sumatera Province Roads in Mandailing Natal Regency - Hasibuan, Asrul Hanafi; Ridwan, M.; Hasibuan, Gina Cynthia Raphita (Universitas Ibn Khaldun Bogor, 2025)
From www.portibinews.com regarding the Audit Results Report of the North Sumatra Representative Audit Agency which was issued on May 26 2022 that the work at the North Sumatra Province Public Works and Spatial Planning Service in the 2020 budget year was Improvement of the Provincial Road Structure of the Jembatan Merah – Muarasoma Road Section in Mandailing Natal Regency there is a lack of volume and a lack of quality of work. The physical inspection of this work was carried out together with the Budget User Authority (KPA), the Activity Technical Implementation Officer (PPTK), the Supervisory Consultant, and the North Sumatra Province Inspectorate. This is the basis for this study to analyze the Critical Success Factor (CSF), identify CSFs that have a significant effect on the success of the implementation of asphalt paving work on North Sumatra Province roads in Mandailing Natal Regency and analyze the effect of CSFs on the achievement of performance indicators. The Partial Least Square - Structural Equation Modeling (PLS-SEM) analysis method is used in this study to analyze the CSF performance of the implementation of asphalt paving work on North Sumatra Province roads in Mandailing Natal Regency. This analysis method uses the help of Smart PLS software. PLS-SEM is more suitable for developing exploratory research that has limited theory development and PLS-SEM is also more suitable for use if the research data is ordinal (eg: Likert scale) and nominal and ignores normally distributed data (nonparametric). The results of the analysis show that the Critical Success Factor that has an impact on the success of the implementation of asphalt paving work on North Sumatra Province roads in Mandailing Natal Regency is the supervision factor with a value of 0.406 having the greatest impact. Other factors such as labor factors (0.281), environmental standard factors (0.228), quality test standard factors (0.214), equipment factors (0.176) have a moderate impact, while design error factors (0.109), material factors (0.088), work method factors (0.026) have a small impact. On the other hand, the factors that significantly influence the success of the implementation of asphalt paving work on North Sumatra Province roads in Mandailing Natal Regency in achieving performance indicators are the work method factor (X4), the quality test standard factor (X5), the environmental standard factor (X6), the supervision factor (X7), and the design error factor (X8). Overall, the Critical Success Factor factors for the performance of the implementation of asphalt paving work on North Sumatra Province roads in Mandailing Natal Regency influence the success in achieving performance indicators by 15.3%, while other variables outside this regression model influence the rest (100 - 15.3 = 84.7%).